Mutu Pelayanan Keperawatan terhadap Tingkat Kepuasan Pasien Rawat Inap di Rumah Sakit (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the relationship between the quality of nursing services and the level of satisfaction of inpatients in a hospital. The method used is a descriptive approach with descriptive statistical analysis. The results showed that all respondents gave the same assessment of service quality (score 36) and patient satisfaction (score 50) with a standard deviation of 0, indicating a homogeneous perception. This indicates that the quality of nursing services and patient satisfaction are at a high and uniform level. However, the uniformity of the data indicates the need for a more sensitive instrument to detect variations in respondents' perceptions. The conclusion is that the quality of nursing services has a positive effect on patient satisfaction.  Keywords: Patient satisfaction, Quality of nursing services, Health services, Hospitals